Analyzing the natural resource extension needs of Spanish-speakers: A perspective from Florida (2011)
Hispanics are the country's fastest growing minority group. The study reported here surveyed and assessed Extension agents from two demographically different regions in Florida on perceptions and attitudes about the need, quality, and dissemination of Spanish Extension materials. Results showed Extension programs are important sources of information for Spanish-speakers from a region with a high population of Hispanics. However, Extension agents do not feel adequately prepared to reach this audience, and resources are insufficient, especially on critical environmental topics relevant to the audience. The study demonstrates the need to develop regionally and culturally relevant Spanish Extension materials for urban Spanish-speakers.